2020
DOI: 10.1002/jor.24909
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning improves muscle regeneration after ischemia–reperfusion injury

Abstract: Ischemia-reperfusion injury (IRI) is a critical condition associated with serious clinical manifestations. Extensive research has focused on the strategies increasing organ tolerance to IRI. Preconditioning (PC) has been shown to provide protection to various organs toward IRI. However, the underlying mechanisms remain unknown. This study aimed to evaluate the role of PC on muscle regeneration after IRI and the potential underlying mechanisms. Three-month-old male UCP-1 reporter mice underwent unilateral hindl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Preconditioning muscle before ischemic injury has been shown to improve muscle quality and function in mice as well as increase uncoupling protein 1–positive beige adipose FAP differentiation. 35…”
Section: Discussionmentioning
confidence: 99%
“…Preconditioning muscle before ischemic injury has been shown to improve muscle quality and function in mice as well as increase uncoupling protein 1–positive beige adipose FAP differentiation. 35…”
Section: Discussionmentioning
confidence: 99%
“…We have additionally demonstrated that FAPs likely have an important role in this degenerative process given their increase in adipogenic and fibrotic gene expression noted at 6 weeks, coinciding with worsening fibrofatty degeneration of muscle by 15 weeks. The implication of FAPs in the pathogenesis of lumbar multifidus degeneration is significant, because FAPs represent a large endogenous stem cell population within muscle that can be harnessed under the proper treatment conditions to improve muscle quality after injury [ [13] , [14] , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…At 6 weeks (n = 4/group), 8 weeks (n = 4/group), 10 weeks (n = 4/group), and 12 weeks (n = 4/group) postoperatively, mice underwent DigiGait analysis (Mouse Specifics, Framingham, MA) to quantify changes in the gait patterns of the right and left hindlimbs as previously described [16] , [17] .…”
Section: Methodsmentioning
confidence: 99%
“…The mice were randomly divided into Control group and MAP group ( n = 6 in each group). Mice in both groups underwent unilateral hindlimb ischemia with a rubber band on the base of right thigh for 3 h as previously described 11 . The other hindlimb was used as Contralateral side.…”
Section: Methodsmentioning
confidence: 99%
“…Mice in both groups underwent unilateral hindlimb ischemia with a rubber band on the base of right thigh for 3 h as previously described. 11 The other hindlimb was used as Contralateral side. The application of MAP treatment was performed on the same hindlimb at 1 week after the initial injury by using a compact electromagnetic unit with an unfocused acoustic pulse source (LiteMed Inc.).…”
Section: Animals and Proceduresmentioning
confidence: 99%